Season of the swamp : a novel - Herrera, Yuri, 1970- (Graywolf Press, 2024)
"New Orleans, 1853. A young exile named Benito Juárez disembarks at a fetid port city at the edge of a swamp. Years later, he will become the first indigenous head of state in the postcolonial Americas, but now he is as anonymous and invisible as any other migrant to the roiling and alluring city of New Orleans. Accompanied by a small group of fellow exiles who plot their return and hoped-for victory over the Mexican dictatorship, Juárez immerses himself in the city, which absorbs him like a sponge. He and his compatriots work odd jobs, suffer through the heat of a southern summer, fall victim to the cons and confusions of a strange young nation, succumb to the hallucinations of yellow fever, and fall in love with the music and food all around them. But unavoidable, too, is the grotesque traffic in human beings they witness as they try to shape their future. Though the historical archive is silent about the eighteen months Juárez spent in New Orleans, Yuri Herrera imagines how Juárez's time there prepared him for what was to come. With the extraordinary linguistic play and love of popular forms that have characterized all of Herrera's fiction, Season of the Swamp is a magnificent work of speculative history, a love letter to the city of New Orleans and its polyglot culture, and a cautionary statement that informs our understanding of the world we live in"--